From health literacy to organ donation and transplantation awareness: The path through self-control - Huseynov, Amil; Satici, Begum (BAISHIDENG PUBLISHING GROUP INC, 2025)
BACKGROUND Organ donation and transplantation are vital for saving lives, yet awareness remains limited. Health literacy, the ability to understand and use health information, and self-control, which influences decision-making, are crucial factors in promoting awareness. Understanding their relationship can guide efforts to increase participation in organ donation. AIM To investigate the effect of health literacy on organ donation and transplantation awareness, with self-control acting as a mediator, and to emphasize its importance. METHODS The study comprised 345 adults recruited from five different cities in T & uuml;rkiye. The sample included 208 women (60.29%) and 137 men (39.71%). The age range of the sample group varies between 18 and 49 (median age = 24.13; SD = 8.81). Self-report data were collected including psychometric measures assessing organ donation and transplantation awareness, health literacy, and self-control. Reliability analysis, descriptive statistics, correlational analysis, and mediational analysis of the data were carried. RESULTS The analysis showed that health literacy was positively correlated with organ donation and transplantation awareness (r = 0.340) and self-control (r = 0.376). Self-control was positively related to organ donation and transplantation awareness (r = 0.531). Mediating analysis supported a mediation model where health literacy was found to influence organ donation and transplantation awareness via self-control (bootstrap = 0.158, 95% confidence interval = 0.105-0.215). CONCLUSION The results indicate that self-control mediates the positive relationship between health literacy and organ donation and transplantation awareness. Enhancing individuals' health literacy may therefore increase awareness of organ donation and transplantation through improvements in self-control.
Keywords: Health literacy; Organ donation; Organ transplantation; Self-assessments; Mediation; EGO DEPLETION; MODEL; Psychiatry